Burden and survival of colorectal cancer in china from 1990 to 2021: findings from the global burden of disease study - Boyuan Ma (The Lancet Regional Health. Western Pacific)
Background: Colorectal cancer is a global health challenge due to its high incidence and mortality. In 2021, it was the second most diagnosed cancer and cause of cancer-related deaths worldwide. Risk factors include genetics, poor diet, obesity, and inflammatory conditions. Early detection significantly improves survival, with localized cancer showing over 90% of five-year survival. Screening programs like colonoscopy are vital for early diagnosis. Methods: This study utilized data from the Global Burden of Diseases (GBD) 2021 to analyze colorectal cancer burden in China and globally. Using DisMod-MR 2.1, the study mapped colorectal cancer estimates to ICD-10 codes C18-C21. Incidence, prevalence, mortality, and DALYs were extracted and five-year relative survival rates were calculated using the formula (1–mortality/incidence) × 100 to assess cancer burden and survival in China. The study used age-standardized rates (ASR) to ensure comparability across regions and sexes. It calculated percentage changes and average annual percentage change (AAPC) to assess trends from 1990 to 2021. Decomposition analysis explored factors influencing changes, with significance tested via 95% confidence intervals. Findings: In 2021, colorectal cancer in China accounted for 3.61 million cases and 6.85 million DALYs, representing 30.9% and 28.1% of global totals, respectively. The age-standardized prevalence and DALY rates were 168.62 and 331.73 per 100,000, respectively. China reported 658,321 new cases and 275,129 deaths, with age-standardized rates of 31.44 for incidence and 13.64 for mortality. Compared to 21 regions, China had lower age-standardized rates for prevalence, incidence, deaths, and DALYs. From 1990 to 2021, the number of colorectal cancer cases and deaths increased by 315.63% and 130.61%, respectively. The age-standardized incidence rate rose by 1.66% annually, while the mortality rate fell by 0.41%. Males had higher rates than females across all metrics. The increase in incidence and prevalence was largely due to epidemiological changes, while deaths and DALYs were driven by population aging. In 2021, the five-year relative survival rate was 58.21%, with slightly higher rates for males (58.38%) than females (57.91%). Interpretation: This study analyzed colorectal cancer burden in China from 1990 to 2021, showing increasing incidence, prevalence, deaths, and DALYs, mainly due to epidemiological changes and population aging. The overall 5-year survival rate is 58.21%, with higher rates in males. Rapid economic development and industrialization have led to westernized lifestyle in developing countries, like China, characterized by unhealthy diets, sedentary behaviors, insufficient physical activity, and substance abuse. These factors may contribute to the prementioned significant rise in colorectal cancer burden in China. Despite this, the age-standardized mortality and DALY rate decreased with AAPCs of -0.41% and -0.53%, respectively, reflecting improvements in early detection and advancements in technology and referral practices. It is imperative for public health initiatives to address these lifestyle factors and promote early screening to mitigate the growing burden of colorectal cancer. These findings highlight the need for targeted public health strategies and provide insights into sex and age-related variations, aiding in the development of effective nationwide interventions in China.